Geochemical and sedimentological record of sediment core TRI1 retrieved from Lake Trichonida (southern Greece) - Joana Seguin; Pavlos Avramidis; Walter Dörfler; Alexandros Emmanouilidis; Ingmar Unkel (PANGAEA, 2020)
In spring 2018, the sediment core TRI1 (38°33 extquotesingle0.61" N, 21°35 extquotesingle20.76" E) was retrieved from 50m water depth in the central eastern part of Lake Trichonida, the largest Greek lake, using a high-precision wire-operated piston corer system (Usinger system). The here presented TRI1 master core sequence covers 438 cm (sedimentary units 9 - 19). The core was scanned at 1 mm resolution with an Avaatech X-ray Fluorescence (XRF) core scanner and the raw data presented here is displayed as element counts per second (cps). RGB colour values were taken with a digital line scan camera to depict colour variation with depth. The concentrations of total nitrogen (TN), total organic carbon (TOC), and total inorganic carbon (TIC) were determined on 21 dried, grinded, and homogenized samples through combustion in an elemental analyzer (Euro EA, Elementanalyzer). AMS radiocarbon (14C) dates were processed at the Poznań Radiocarbon Laboratory. The core sequence covers the last 2600 years and was analysed to reconstruct ecosystem and landscape changes as well as palaeoclimatic fluctuations in SW Greece.